2012
DOI: 10.1161/circgenetics.112.963314
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Evaluating Lipoprotein-Associated Phospholipase A 2 Mass and Activity at Baseline and After Rosuvastatin Therapy

Abstract: Background— Lipoprotein-associated phospholipase A 2 (Lp-PLA 2 ) is a proinflammatory enzyme bound to low-density lipoprotein cholesterol and other circulating lipoproteins. Two measures of Lp-PLA 2 , mass and activity, are associated with increased cardiovascular risk. Data are sparse regarding genetic determinants of Lp-PLA 2 mass and activity, and no prior data are avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
(43 reference statements)
3
20
0
Order By: Relevance
“…The 1-LOD limit identified a region 0.78 Mbp in length containing C14orf177 and Mir_320, both of which have some support for involvement in dementia-related disease and processes. C14orf177 for instance, has been associated with risk for amyotrophic lateral sclerosis [29] and lipoprotein cholesterol levels [30], while members of the mir-320 microRNA family are significantly altered in sporadic AD brains [31] and associated with both neurite outgrowth [32] and neurodegeneration [33]. Evidence for genomic features with regulatory potential such as several ESTs and lincRNAs also exists in the region (based on UCSC genome browser data)[26], including one lincRNA in particular, TCONS_12_00008237, which is highly expressed in brain [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The 1-LOD limit identified a region 0.78 Mbp in length containing C14orf177 and Mir_320, both of which have some support for involvement in dementia-related disease and processes. C14orf177 for instance, has been associated with risk for amyotrophic lateral sclerosis [29] and lipoprotein cholesterol levels [30], while members of the mir-320 microRNA family are significantly altered in sporadic AD brains [31] and associated with both neurite outgrowth [32] and neurodegeneration [33]. Evidence for genomic features with regulatory potential such as several ESTs and lincRNAs also exists in the region (based on UCSC genome browser data)[26], including one lincRNA in particular, TCONS_12_00008237, which is highly expressed in brain [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…These results might indicate that Lp-PLA2 activity was not involved in MS and disease progression. It was reported that there were differential associations of Lp-PLA2 mass and activity in vascular events [21]. In our study we did not measure Lp-PLA2 mass which was one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 80%
“…More samples were also needed to study the effect of A379V. Besides, we only studied three SNPs of PLA2G7, while more polymorphisms in the gene should be evaluated due to the possibility that other SNPs demonstrated subsequently as affecting Lp-PLA2 activity (Chu et al 2012;Grallert et al 2012;Suchindran et al 2010) could improve the precision of PLA2G7 genotyping in predicting CHD. These findings remain to be further validated in more studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that genetic factors accounted for approximately 60 % of factors influencing activity of plasma Lp-PLA2 (Guerra et al 1997). Previous genome-wide association studies (GWAS) have revealed several single nucleotide polymorphisms (SNPs) that affect lipoprotein-associated phospholipase A2 (Lp-PLA2) activity or levels (Chu et al 2012;Grallert et al 2012;Suchindran et al 2010), which contributes much to our final selection of the PLA2G7 SNPs. Among polymorphism loci associated with CHD, there have been reports mostly about nonsynonymous polymorphisms with R92H, V279F, I198T, and A379V.…”
Section: Introductionmentioning
confidence: 99%